تقييم أداء المصارف الإسلامية وفق بطاقة الأداء المتوازن -دراسة حالة مصرف السلام الجزائري -: Evaluating the performance of Islamic banks according to the blanced scorecard – case study of the Algerian Salama Bank – - خنوسة عديلة; فوضيل لحسن (Journal of North African Economies, 2025)
The main objective of the study is to find out how the performance of Islamic banks is evaluated according to the balanced scorecard, with a case study of the Algerian Salam Bank during the four years from 2018 to 2021. In order to reach that goal, the deductive approach was followed with its two tools of description and analysis, and some results were reached, including: The balanced scorecard should adapt to the specificity of the Islamic bank and add other dimensions that include its developmental and ethical goals, and that the performance of the Algerian Salam Bank was good, and it always seeks to achieve the best and its strategy for customers is successful and good.